1988
DOI: 10.1093/nar/16.5.1903
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens and growth factors induce the mRNA of the 52K-pro-cathepsin-D secreted by breast cancer cells

Abstract: The estrogen-induced 52K protein secreted by human breast cancer cells is a lysosomal protease recently identified as a pro-cathepsin D by sequencing several cDNA clones isolated from MCF7 cells (Augereau et al., Mol. Endocr.). Using one of these clones, we detected, in MCF7 cells, a 2.2 kb mRNA whose level was rapidly increased 4- to 10-fold by estradiol, but not by other classes of steroids. Other mitogens, such as epidermal growth factor and insulin, also induced the 2.2 kb mRNA in a dose-dependent manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
46
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(52 citation statements)
references
References 26 publications
6
46
0
Order By: Relevance
“…RIA for cathepsin D. The commercially available ELSA cath-D kit consisted of ELSA tubes coated with the anti-cathepsin-D monoclonal antibody (8,39); 300 l of monoclonal 125 I-labeled anti-cathepsin-D antibody and then 50 l of sample (medium or cytosolic extract) were added to each tube. This mixture was then incubated at 25ЊC with shaking in an incubator shaker for 3 h. The tubes were then washed three times with 3 ml of Tween 20 solution after the contents in the tube were removed by aspiration.…”
Section: Chemicalsmentioning
confidence: 99%
“…RIA for cathepsin D. The commercially available ELSA cath-D kit consisted of ELSA tubes coated with the anti-cathepsin-D monoclonal antibody (8,39); 300 l of monoclonal 125 I-labeled anti-cathepsin-D antibody and then 50 l of sample (medium or cytosolic extract) were added to each tube. This mixture was then incubated at 25ЊC with shaking in an incubator shaker for 3 h. The tubes were then washed three times with 3 ml of Tween 20 solution after the contents in the tube were removed by aspiration.…”
Section: Chemicalsmentioning
confidence: 99%
“…Bergeron et al (10) studied extensively as an in vitro and in vivo model of estrogen-dependent breast cancer and displays multiple estrogendependent gene expressions (15). Estrogendependent preconfluent cell proliferation in specific strains has been used as a marker for estrogenicity (16).…”
Section: Introductionmentioning
confidence: 99%
“…We tested ERa, shown to be downregulated by E2, and progesterone receptor (PgR), Cathepsin D and pS2, all of which have been shown to be upregulated by E2 in MCF-7 cells (Read et al, 1989;Nardulli et al, 1988;Cavailles et al, 1988;Weaver et al, 1988). We have previously demonstrated that the loss of PgR regulation by E2 attests for the loss of ER function Saceda et al, 1996).…”
mentioning
confidence: 99%